2004
DOI: 10.1074/jbc.m401530200
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Bax Activation and Apoptotic Response to Microtubule-damaging Agents by p53 Transcription-dependent and -independent Pathways

Abstract: Microtubule-damaging agents (MDA) are potent antineoplastic drugs that are widely used in clinical treatment for a variety of cancers. However, the precise mechanisms underlying MDA-induced cell death are largely unknown. Here, we report that both p53 and Bax are central participants in the MDA-mediated cell death machinery in HCT116 human colon cancer cells. MDA, including epothilone B analogue (BMS-247550) and vinblastine, induced apoptosis of Bax-positive HCT116 cells in a p53-dependent manner; p53 was requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
94
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(103 citation statements)
references
References 52 publications
7
94
1
1
Order By: Relevance
“…Moreover, ixabepilone-induced apoptosis was associated with activation of caspase-2 whereas taxanes were associated with caspase-9 activation (51). Consistent with these results, ixabepiloneinduced apoptosis in breast cancer cells was also shown to occur through p53-dependent activation of Bax (52). However, in breast cancer cells, p53-dependent activation of Bax was shown to occur via transcription-dependent (elevated expression of PUMA) and transcription-independent (direct translocation of p53 to the mitochondria) mechanisms (Table 3; ref.…”
Section: Epothilone B Analog Ixabepilonesupporting
confidence: 66%
“…Moreover, ixabepilone-induced apoptosis was associated with activation of caspase-2 whereas taxanes were associated with caspase-9 activation (51). Consistent with these results, ixabepiloneinduced apoptosis in breast cancer cells was also shown to occur through p53-dependent activation of Bax (52). However, in breast cancer cells, p53-dependent activation of Bax was shown to occur via transcription-dependent (elevated expression of PUMA) and transcription-independent (direct translocation of p53 to the mitochondria) mechanisms (Table 3; ref.…”
Section: Epothilone B Analog Ixabepilonesupporting
confidence: 66%
“…Although the precise mechanism by which Bax and Bak regulate DATS-induced cell death remains elusive, it is possible that DATS treatment causes conformation change and oligomerization of Bax/Bak leading to their translocation to the mitochondria. This possibility is likely based on following considerations: (a) Bax activation by certain apoptotic stimuli is dependent on ROS generation (38), which is observed in DATS-treated prostate cancer cells (present study), and (b) microtubuledamaging agents have been shown to cause Bax activation (48), and DATS treatment is known to disrupt tubulin network (18). However, further studies are needed to systematically explore this possibility.…”
Section: Discussionmentioning
confidence: 79%
“…These findings support that p53 does not interact with Bax/Bak and that p53-Bax or p53-Bak interaction may not be critical for resveratrolinduced cytochrome c release in cancer cells. It has been reported that wild type p53 as well as mutant p53 can promote Bax activation on mitochondria (80,81), whereas other studies suggest that p53 translocation to mitochondria does not induce Bax activation and apoptosis (82,83). Expression of mutant p53 in cancer cells confers selective advantage and resistance to apoptosis (84 -86).…”
Section: Discussionmentioning
confidence: 99%